2018
DOI: 10.3389/fgene.2018.00132
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Landscape Distinguishes the Genomic Loci of Hundreds of Androgen-Receptor-Associated LincRNAs From the Loci of Non-associated LincRNAs

Abstract: Cell signaling events triggered by androgen hormone in prostate cells is dependent on activation of the androgen receptor (AR) transcription factor. Androgen hormone binding to AR promotes its displacement from the cytoplasm to the nucleus and AR binding to DNA motifs, thus inducing activatory and inhibitory transcriptional programs through a complex regulatory mechanism not yet fully understood. In this work, we performed RNA-seq deep-sequencing of LNCaP prostate cancer cells and found over 7000 expressed lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 100 publications
(150 reference statements)
1
9
0
1
Order By: Relevance
“…1c, blue and red bars). Also interesting, prostate tumor suppressor lincRNA DRAIC [40], previously detected by us with RIP-seq as one of the other RNAs associated with AR [18], was confirmed here by RIP-qPCR ( Fig. 1d, blue and red bars), whereas negative control snRNA U1-19 was not associated with AR ( Fig.…”
Section: Pvt1 Associated With Ar and With Prc2 In Lncap Cellssupporting
confidence: 80%
See 2 more Smart Citations
“…1c, blue and red bars). Also interesting, prostate tumor suppressor lincRNA DRAIC [40], previously detected by us with RIP-seq as one of the other RNAs associated with AR [18], was confirmed here by RIP-qPCR ( Fig. 1d, blue and red bars), whereas negative control snRNA U1-19 was not associated with AR ( Fig.…”
Section: Pvt1 Associated With Ar and With Prc2 In Lncap Cellssupporting
confidence: 80%
“…Regarding the possible interplay between AR and lncRNAs, two studies have demonstrated AR association with HOTAIR [ 16 ], PCGEM and PRCNR1 [ 17 ] lncRNAs in PCa. Our group has recently shown that in LNCaP cells the AR is significantly associated with over six hundred other lncRNAs [ 18 ]. Interestingly, the oncogenic lncRNA PVT1 was one of the RNAs that was associated with AR, a finding that was not explored in that work [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result AR signaling devolves from its normal control of cell growth and differentiation to favor growth promoting pathways 6,7 . In this manner AR signaling is "re-wired", often associated with distorted histone modifications and DNA methylation patterns that impact AR access to enhancer regions 8,9 . These observations fit with the emerging concept of oncogenic enhancer addiction 10,11 acting as a driver of lineage plasticity 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Com a descoberta dos RNAs longos não codificadores, descritos mais abaixo nesta introdução, os fatores que influenciam a transcrição gênica também passaram a incluí-los (Davidson and Britten 1979, Consortium, Birney et al 2007, Mercer, Dinger et al 2009, Consortium 2012, Rinn and Chang 2012, Cheetham, Gruhl et al 2013, Iyer, Niknafs et al 2015). Com relação ao AR, já há estudos demonstrando a associação do receptor de andrógeno aos RNA longos não codificadores HOTAIR, PCGEM, PRCNR1 (Yang, Lin et al 2013, Zhang, Zhao et al 2015) e nosso grupo mostrou recentemente que o AR se liga a um conjunto de algumas centenas de outros lncRNAs (daSilva, Beckedorff et al 2018).…”
Section: Geneunclassified